Miniaturized-specimen creep testing: an alternative for evaluating the remaining life of Cr-Mo steel components - Heloisa Cunha Furtado; Fernanda Figueiredo Martins dos Santos; Leonardo Sales Araújo; Levi de Oliveira Bueno (Academia Materials Science)
Creep is the main degradation mechanism in steel and superalloy components operating at high temperatures in thermal and nuclear power generation units. Therefore, acquiring creep data during equipment operation is vital for a realistic calculation of the remaining useful life of these units. However, there are severe limitations to obtaining sufficient material for standard-size specimen fabrication and representative sample of the component. Therefore, replacing conventional specimens with small-size specimens, which can be fabricated from a limited amount of material, can facilitate the assessment of power plant components by creep tests without any structural damage. This study aims to compare creep-test results of Cr-Mo ferritic steel using conventional and small-size specimens to assess the effectiveness of using miniaturized specimens for analysis. The results of this study confirm the applicability of miniaturized-specimen creep testing for the reliable estimation of the materials’ remaining life. The results also emphasize the importance of carrying out creep test on miniaturized samples under vacuum, to avoid harmful effects due to the formation of the oxide layer.